Charles Taylor and Liberia ambition and atrocity in Africa?s Lone Star State - Waugh, Colin M. (London Zed Books, 2011)
Campaigner, insurgent, arms dealer, warlord, commodity trafficker, elected president, international fugitive, and finally prisoner, Charles Taylor sought to lead his native Liberia to change but instead destroyed it in a frenzy of violence, greed, and uncontrolled personal ambition. In the process, he threw much of Liberia's neighboring region into turmoil for over a decade, finally facing judgment in The Hague for his role in the Sierra Leone conflict.
Includes bibliographical references (p. [360]-363)
Keywords: aylor, Charles Ghankay